Morphology and Molecular Phylogeny of Four Trachelocercid Ciliates (Protozoa, Ciliophora, Karyorelictea) Found in Marine Coastal Habitats of Northern China, With Description of a New Genus, Two New Species and a New Combination - Ma, Mingzhen; Li, Yuqing; Ma, Honggang; Al-Rasheid, Khaled A. S.; Warren, Alan; Wang, Yurui; Yan, Ying (Frontiers in Marine Science, 2021)
The morphology of four trachelocercid ciliates, Foissnerella typica gen. nov., spec. nov., Trachelolophos monocaryon (Dragesco, 1965) comb. nov. (original combination: Tracheloraphis monocaryon Dragesco, 1965), Tracheloraphis katzae spec. nov. and Tracheloraphis colubis (Kahl, 1933) Xu et al., 2011, were studied in live and protargol-stained specimens. All samples were isolated from the intertidal zone of sandy beaches at Qingdao, China. The new genus Foissnerella can be distinguished from other trachelocercid genera mainly by the three circumoral kineties each composed of a row of dikinetids and the absence of a brosse or ciliary tuft in the oral cavity. The detailed investigation on the poorly described Tracheloraphis monocaryon Dragesco, 1965 reveals that its oral infraciliature includes one uninterrupted circumoral kinety and a conspicuous ciliary tuft in the center of the oral cavity, which is consistent with the genus Trachelolophos rather than Tracheloraphis. Therefore, this species is transferred to Trachelolophos as Trachelolophos monocaryon (Dragesco, 1965) comb. nov. Tracheloraphis katzae spec. nov. can be recognized by the combination of its minute brownish cortical granules and 9–15 somatic kineties. The small subunit (SSU) rDNA of each species was sequenced for the first time. Phylogenetic analyses of the SSU rDNA show that Foissnerella typica clusters with Apotrachelocerca arenicola (Kahl, 1933) Xu et al., 2011 in a group that is sister to all other trachelocercids.